Reducing waste heat to the minimum: Thermodynamic assessment of the M-power cycle concept applied to micro Gas Turbines. (1st December 2020) - De Paepe, Ward; Pappa, Alessio; Montero Carrero, Marina; Bricteux, Laurent; Contino, Francesco
Abstract: To fully embrace its opportunities in future decentralized power production, the current mGT has to become more flexible in terms of operation, i.e. decoupling heat and power production. Cycle humidification during periods with low heat demand is a possible route to handle this issue. Indeed, cycle humidification has already been proven to increase the mGT electrical efficiency. Nevertheless, even when applying the most advanced humidified cycle concept, i.e. the REgenerative EVAPoration cycle, the electrical performance increase remains rather limited. In this perspective, the more recent Maisotsenko (or M-power) cycle concept offers a larger potential for humidification, even though its potential was only proven on large-scale gas turbine cycles and never applied to the smaller mGT scale. In this paper, the concept of this M-power cycle is applied to a 100 kWe mGT (Turbec T100) to assess its performance, using Aspen Plus® simulations. Moreover, the impact of various inputs, component performance and control parameters is studied using a sensitivity analysis. The numerical results highlight that the M-power cycle has the highest waste heat recovery and thus the highest electric efficiency (up to 147 kWe electric power output with an electric efficiency of 42.1% at constant rotational speed and 41.1%, corresponding to an 8.3%point absolute increase, at constant power output). Moreover, this cycle concept allows to approach the thermodynamic limit for cycle humidification. Indeed, a large exergy destruction is avoided by not going for direct water injection, but rather using a gradual injection and evaporation. Additionally, from a technological point of view, the M-power cycle is also preferable for the small-scale mGT. Indeed, in the M-power cycle, saturation tower, aftercooler, recuperator and economizer are combined in one single component, significantly reducing the complexity of the cycle. The main limitation is the saturator, that requires a wet bulb effectiveness of up to 98% to achieve the simulated performance, which can be technological very challenging. Highlights: Humidifying mGTs increases their operational flexibility but performance is limited. M-Power cycle, combining aftercooler, evaporator, and recuperator, offers a solution. M-power cycle performance was assessed, including sensitivity and exergy analysis. Electric efficiency can be increased; however, 98% wet bulb effectiveness is needed. Superior M-power specific water introduction method does not lead to exergy losses.